Efektivitas Aplikasi Religius, Adaptable, Great, Educate, Modern (RAGEM) Sebagai Bentuk Pelayanan Publik Dalam Konteks E-Government - H. Holifah; Ronni Juwandi (Universitas Warmadewa, 2024)
The development of technology and information makes it possible to disseminate information in a matter of seconds, thereby changing the government's mindset in providing public services so that it can meet the needs of the community efficiently. Banten Province, especially Serang City as the capital, has launched the RAGEM Application as a form of e-Government based public service. This research aims to determine the effectiveness of the RAGEM application managed by the Information and Communication Office (Diskominfo) of Serang City as a form of e-government-based public service. The research problems formulated in this study are: (1) How is the public's knowledge of the RAGEM application? (2) What is the effectiveness of the RAGEM application as a form of public service in the context of e-government in Serang City? (3) What is the Evaluation and Strategy of Diskominfo Serang City in developing the RAGEM application? This research uses a qualitative method with a descriptive design. The subjects of this study are the staff of the e-government field of Diskominfo Serang City and the citizens of Serang City who use services at Diskomnfo Serang City. The data analysis technique involves data collection, data reduction, data presentation, and data verification. The results of this research indicate that the RAGEM application as an e-government-based public service is effective, as seen from the indicators of goal achievement, integration, and adaptation that have been running well. However, there are aspects that need improvement, as observed from the limited knowledge of Serang City residents regarding the RAGEM application. In response to this, Diskominfo Serang City has conducted internal evaluation, particularly in terms of service integration from various government agencies and the enhancement of application features, as well as a strategy for equalizing socialization to ensure information reaches all layers of Serang City society.